EVALUASI KETAATAN PENYAJIAN DAN PENGUNGKAPAN LAPORAN AUDITAN BERDASARKAN PSA NO. 29 DENGAN PENDEKATAN DISCLOSURE INDEX PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Fitriani, Ulfatul (Fakultas Ekonomi Universitas Kanjuruhan Malang, 2014)
Statements audited is needed either by the company, the parties outside the company and the auditors themselves. Audited report is a means to communicate the audit work and audit findings in a comprehensive manner, which is given by the audit team to the company. This study aimed to evaluate compliance presentation and disclosure statements audited by PSA No. 29 disclousure index approach in companies listed on the Indonesia Stock Exchange in 2011 until 2012. The sample was financial statements audited industrial manufacturing consumer goods food and beverage sub- sector in 2011 until 2012. This research is a descriptive qualitative data analysis techniques using the disclosure index. The analysis showed that the rate of Disclosure Index presentation and disclosure of audited statements in 2011 and 2012 figures are still below 50%. The results of this study indicate that the manufacturing companies listed on the Indonesia Stock Exchange is not present and express information in its financial statements in full. In other words, the manufacturing companies have not had exposure to the interested parties within the company.